Removal of Aqueous Para-Aminobenzoic Acid Using a Compartmental Electro-Peroxone Process - Donghai Wu (MDPI AG, 2021)
The presence of emerging contaminant para-aminobenzoic acid (PABA) in the aquatic environment or drinking water has the potential to harm the aquatic ecosystem and human health. In this work, the removal of aqueous PABA by a compartmental electro-peroxone (E-peroxone) process was systematically investigated from the kinetic and mechanism viewpoints. The results suggest that single electrolysis or ozonation was inefficient in PABA elimination, and the combined E-peroxone yielded synergistic target pollutant degradation. Compared to the conventional E-peroxone oxidation, the sequential cathodic reactions, followed by anodic oxidations, improved the PABA removal efficiency from ~63.6% to ~89.5% at a 10-min treatment, and the corresponding pseudo first-order kinetic reaction rate constant increased from ~1.6 × 10−3 to ~3.6 × 10−3 s−1. Moreover, the response surface methodology (RSM) analysis indicated that the appropriate increase of inlet ozone concentration, applied current density, initial solution pH value, and solution temperature could accelerate the PABA degradation, while the excess of these operational parameters would have a negative effect on the treatment efficiency. The comparation tests revealed that the coupling of electrolysis and ozonation could synergistically produce hydroxyl radicals (HO•) and the separation of cathodic reactions and anodic oxidations further promoted the HO• generation, which was responsible for the enhancement of PABA elimination in the compartmental E-peroxone process. These observations imply that the compartmental E-peroxone process has the potential for aqueous micropollutants elimination, and the reaction conditions that favor the reactive oxygen species generation are critical for the treatment efficiency.